Local Wisdom in the Edet Mungerje Wedding Tradition of the Gayo Ethnic Group in Southeast Aceh - Lilis Hasan; Hasan Asari (Journal of General Education and Humanities, 2025)
This study explores the Edet Mungerje tradition, a customary wedding ceremony practiced by the Gayo ethnic community in Southeast Aceh Regency, to document its procedures and uncover the embedded values of local wisdom. Despite the rapid influence of modernization and technological advancement, this tradition remains a meaningful and practiced cultural heritage among the Gayo people. Employing a qualitative research approach, data were collected through in-depth interviews with five bridal couples and two traditional leaders. The findings reveal that while several procedural aspects of the ceremony have been simplified or adjusted to fit contemporary lifestyles, the core stages—munginte (marriage proposal), betelah (negotiation of dowry and terms), mujule mas (advice and acceptance), berguru (marital guidance), and mah kero opat ingi (post-wedding family visit)—are still preserved. These stages fulfill ceremonial purposes and transmit local values such as cooperation, deliberation, respect, moral education, and social responsibility. The novelty of this research lies in its contribution to preserving the cultural identity of an ethnic tradition that is at risk of being forgotten. This study offers a framework for cultural preservation amidst globalization. However, the study’s scope is limited to one district and may not fully reflect variations in other Gayo regions. Future comparative studies are recommended to explore inter-ethnic and inter-regional differences in wedding traditions across Aceh. Ultimately, Edet Mungerje serves as a cultural ritual and a vehicle for the intergenerational transmission of noble values.